Peran Komunikasi Dalam Membangun Tim Sumber Daya Manusia Yang Efektif Di Era Digital - Sarif, Devri Pramesti; Gappar, Sumarni; Eliyanti Agus Mokodompit, Patta Haji Nanrang, (STIE AMKOP, 2025)
In the ever-evolving digital era, the challenges in building an effective human resources (HR) team are increasingly complex, especially in terms of communication. This article discusses how effective communication is a key factor in forming and developing a productive HR team that is adaptive to technological change. Communication is not only a means of exchanging information, but also as a tool to build trust, collaboration, and a positive work culture. This study uses a qualitative approach with a literature review to identify relevant and effective communication strategies in a digital work environment. The results of the discussion showed that the use of communication technology, communicative leadership, and information disclosure greatly contributed to team performance. Therefore, organizations need to design an adaptive and inclusive internal communication strategy to face HR challenges in the digital era. Keywords: Communication, Human Resources, Digital Age, Team Collaboration